DESCRIPTION OF THE ADVERSE EVENTS FOLLOWING IMMUNIZATION (AEFI) PFIZER VACCINE IN THE COMMUNITY IN PUSKESMAS UMBUL HARJO I, YOGYAKARTA - Nessy Anggun Primasari; Erika Nurwidiyanti; Indah Nur Widiyanti; Fera Erlita; Ari Setyari; Maria Fatima Rini Wulandari (Jurnal Keperawatan Respati Yogyakarta, 2023)
The Covid-19 pandemic which has an impact on the health system in all countries. The implementation of government policies as an effective effort to stop the transmission of COVID-19 is through vaccination. There is no vaccine that is 100% safe and without risk which also has adverse reactions known as Adverse Events Following Immunization (AIFI). The aim is to find out the description KIPI of the Pfizer vaccine in the community in the Puskesmas Umbul Harjo I, Yogyakarta City. This research was descriptive with a cross-sectional method, with a sample of 96 people who were taken by purposive sampling and data collection. by observation. Based on the results of this study, the proportion of AIFI cases of the Pfizer Covid-19 vaccine was divided into three categories, namely mild local AIFI, mild systemic AIFI and severe AIFI. Based on the number of respondents experiencing mild local AEFIs, there were 56 people (60.22%), respondents who experienced systemic AEFIs were 37 people (39.78%) but did not get data on respondents who were classified as having severe AEFIs. The conclusion of this study is the characteristics of the emergence of AEFI in respondents who received the Covid-19 vaccination based on age, sex, education, occupation and criteria of AIFI.